Virgilian Reception in the „Sulpiciae Conquestio” - Fratantuono, Lee (Collectanea Philologica, 2025)
The Sulpiciae Conquestio that has been transmitted as part of the Epigrammata Bobiensia is a curious work, one that is replete with intertextual allusions to Virgil’s Aeneid in particular. Close examination of the course of its argument will reveal that its author offers reflections on Virgil’s depiction of the place of war and peace in Roman history, with emphasis on the point that peace can be enervating and corrosive to the Roman polity. The Conquestio thus stands forth as a late Flavian Age commentary on the problems that may result from such seemingly successful initiatives as the implementation of the Pax Augusta.